2009
DOI: 10.1021/ed8000039
|View full text |Cite
|
Sign up to set email alerts
|

Developing Learning Objectives and Assessment Plans at a Variety of Institutions: Examples and Case Studies

Abstract: More meaningful assessment plans are increasingly expected at colleges and universities in the United States. These plans are implemented with the intention of providing faculty with data that can be used to improve courses and programs. This attention to objectives, outcomes, and continuous improvement has emerged in the latest version of the guidelines from the American Chemical Society (ACS) Committee on Professional Training (CPT) (1). The new guidelines request a department's most recent self-evaluation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 3 publications
1
68
0
Order By: Relevance
“…1 Moreover, departments are increasingly expected to report course and program-level measures of student learning for internal accountability and external accreditation. 2 One barrier to the implementation of assessment efforts lies in a perception by many chemistry instructors that the field is laden with the use of jargon terminology, that tends to obfuscate the otherwise laudable goals of improved measurements of student learning. 1,3−5 It is not particularly surprising that chemistry education practitioners remain somewhat uncomfortable with terminology with origins in education research.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1 Moreover, departments are increasingly expected to report course and program-level measures of student learning for internal accountability and external accreditation. 2 One barrier to the implementation of assessment efforts lies in a perception by many chemistry instructors that the field is laden with the use of jargon terminology, that tends to obfuscate the otherwise laudable goals of improved measurements of student learning. 1,3−5 It is not particularly surprising that chemistry education practitioners remain somewhat uncomfortable with terminology with origins in education research.…”
Section: ■ Introductionmentioning
confidence: 99%
“…2, 3 Towns 4 reported an analysis of assessment plans within chemistry departments and derived descriptions for how the development of learning objectives and assessment plans were carried out. This study suggested that assessment plans vary based on the number of students being assessed, the level of assessment (course-level and programmatic), and institutional resources.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although this is a small sample, this suggests that CTLO 5.3 requires change in a typical chemistry degree to ensure that it is taught and assessed. Consistent with this assertion, a US study recommended ethics to be addressed because it was lacking in first and second year chemistry units at Purdue University (Towns, 2010), and a UK medical degree was also found to be deficient in the learning outcome of ethics (Robley, Whittle, & Murdoch-Eaton, 2006).…”
Section: Introductionmentioning
confidence: 95%